Agreement among equine veterinarians and between equine veterinarians and inertial sensor system during clinical examination of hindlimb lameness in horses. (21st July 2019) - Leelamankong, P.; Estrada, R.; Mählmann, K.; Rungsri, P.; Lischer, C.
Summary: Background: Hindlimb lameness evaluation is known to be challenging. Experience is essential for the ability of equine veterinarians to detect lameness. Nevertheless, even an experienced veterinarian is still subject to bias. Objective lameness detecting methods have been established to aid veterinarians. Objectives: 1) To estimate the effect of experience on the interobserver agreement and the agreement between a body‐mounted inertial sensor system (BMISS) and veterinarians on detecting hindlimb lameness, and 2) to estimate the agreement between the BMISS and highly experienced veterinarians on change in lameness after diagnostic analgesia. Study design: Cross‐sectional study. Methods: Twenty‐six horses with hindlimb lameness were evaluated in clinical conditions by clinicians and simultaneously measured by the BMISS. Videos of their lameness examination were recorded and shown to 13 veterinarians from three groups of varying experience for evaluation. The interobserver agreement and the agreement between veterinarians and the BMISS were calculated. Results: Interobserver agreement from all three groups was recorded as 'fair'. The strength of agreement between veterinarians and BMISS was 'fair' for the highly experienced group, 'slight to fair' for the moderately experienced group and 'slight' in the inexperienced group. The BMISS and the highly experienced veterinarians declared a 'strong' agreement in assigning an improvement in lameness after diagnostic analgesia. Main limitations: Lameness evaluation through video viewing might be more challenging for some evaluators than live situations. Conclusions: Given the task of evaluating videos of horses trotting in a straight line, the more experienced veterinarians did not show more reliability than those with less experience. Due to 1) the moderate agreement between the BMISS and clinicians (highly experienced and moderately experienced) in the live clinical evaluation in determining hindlimb lameness, and 2) the strong association between the BMISS and highly experienced veterinarians in determining improvement of lameness after anaesthesia, therefore the use of the BMISS as a supporting tool for veterinarians is encouraged.